Medidas de Bienestar: De lo General a lo Particular - Cárdenas Rodríguez, Oscar Javier (Acta Universitaria, 2008)
This paper analyzes ways of measuring well-being. The study begins with the gross domestic product (GDP) as a measurement of well-being at the national level. It also discusses alternative ways of measuring well-being at the level of aggregates, such as the ecological GDP and the index of human development (HDI). Moreover, some measurements of the microeconomic type, such as income distribution, poverty, and marginalization are analyzed. This research study states that the best indicator of welfare depends on a given specific objective. This is because none of the ways of measuring well-being is able to provide a definite answer to all the questions related to the welfare of a society.